Language, literature and ethnic identity - Šabec, Nada (Annales. Series historia et sociologia, 2016)
The relationship between mother tongue maintenance on the one hand and the sense of ethnic identity in immigrant contexts on the other represents one of the more intriguing issues for researchers. Some see language as a determining feature of ethnic identity, while for others language does not play a central role at all. It is the purpose of this article to explore this very complex and intricate relationship in the case of a small Slovene Canadian community in Vancouver. The fi ndings are based on empirically gathered data; both the instrumental and literary functions of the language are taken into account.
Keywords: ethnic identity; etnična identiteta; first language; književnost; litarature; literature; materinščina; mother tongue maintenance; ohranjanje maternega jezika; Slovenci v Kanadi; Slovene; Slovene Canadians; Slovene lanhuage; slovenščina; Vancouver